ANALISIS KAPASITAS SISI UDARA DAN TERMINAL PENUMPANG BANDAR UDARA JUANDA SURABAYA - , TEGUH ARI RAHMAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Low Cost Carrier concept offers a cheap flight which influence to the increasing of growth of passanger number. It is not only creating queue in the land side but also in the air side. There is lot of airpot in Indonesia that operates over normal capacity, one of them is Juanda Airport Surabaya. For that reason its acquired investigating in order to figure out the capacity both of passenger terminal and air side in Juanda airport, Surabaya. The methods used in this research is FAA and DORATASK in order to measuring runway capacity, the method FAA for capacity of taxiway, the method of Jica and dynamic capacity for Apron. While for terminal capacity use methods SKEP, FAA and JICA. From the data of passenger aircraft, then running projection passenger movement and the plane in 2024. Results of the analysis shows that the capacity of runway 10 (VFR/IFR) is 51/39 movements per hour, and capacity of runway 28 (VFR/IFR) about 52/39with the method FAA, whilethere are 27 movement using methods DORATASK. Taxiway capacity through FAA method is 85 movements per hour. And the Apron capacity is 21 per hour at peak hour with JICA, while using dynamic capacity, the result performed 31 per hour for maximum dynamic capacity and 20 per hour for minimum dynamic capacity. The wider that needed to accommodate the movement existing passenger terminal is 53,531 m2 both of domestically and internationally with JICA, while using methods FAA needed area of 9,150 m2 for domestic and 166,347 m2for the international. Results of the analysis with the method SKEP shows 7 facilities domestic terminal meet the count and 6 facilities terminal has not fulfilled the count. And for the terminal international there are 10 facilities domestic terminal meet up the count and 5 facilities terminal has not fulfilled the count.